ANALISIS PUTUSAN PENGADILAN NIAGA TERKAIT AKIBAT HUKUM PERMOHONAN PKPU YANG DIAJUKAN OLEH PIHAK YANG TIDAK BERWENANG (STUDI KASUS PUTUSAN PENGADILAN NIAGA PADA PENGADILAN NEGERI JAKARTA PUSAT NOMOR 24/PDT.SUS-PKPU/2018/PN.NIAGA.JKT.PST) - Regina Nitami Kasdi; Suyud Margono (Jurnal Hukum Adigama, 2019)
Indonesia is currently developing a rapidly growing economy so that various kinds of debt problems arise due to efforts to increase capital or develop a business. One effort that can be done to resolve this debt and credit problem is to submit a bankruptcy application or PKPU if simple requirements are met as specified in Law No. 37 of 2004. PKPU is an effort made by debtors and creditors with the intention to propose a peace plan which includes offering the payment of part or all of the debt to creditors regarding the settlement of debts between them. In Law No. 37 of 2004 is specifically regulated regarding the party authorized to submit PKPU applications, namely in Article 222 Paragraph (1) regulated that the Parties that can submit PKPU requests are Debtors or Creditors, so PKPU requests may not be submitted by outside parties as specified in the law. Therefore, the problem raised by the author is due to the legal submission of PKPU requests submitted by unauthorized parties in view of Law Number 37 of 2004 Concerning Bankruptcy and Delaying Obligations for Debt Payment. Even though the law has specifically regulated the parties who can submit PKPU requests, there are still PKPU requests submitted by unauthorized parties. The legal consequence of a PKPU petition filed by a party outside of what has been specified in the bankruptcy law and PKPU is that such a request must be rejected by a court judge examining the case.